PENINGKATAN KESADARAN DAN IMPLEMENTASI GREEN MARKETING BAGI UMKM DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN DI KOTA CIREBON - Pranata, Sudadi; Komara, Nandang (ICON Publisher, 2025)
This community service program aims to increase awareness and implementation of green marketing for MSMEs in Cirebon City in supporting sustainable development. Training and mentoring are conducted to provide an understanding of the concept of green marketing and its implementation strategies in business. The results of the activity show that participants experienced increased insight into the benefits of green marketing, both in terms of the environment and business competitiveness. Several MSMEs have begun to implement green marketing strategies by using environmentally friendly raw materials, biodegradable packaging, and sustainability-based communication. The main challenges faced include higher production costs, limited access to green raw materials, and low consumer awareness. Continuous mentoring and support from the government and academics are needed so that the implementation of green marketing can be more effective. Digital marketing is one of the strategies proposed to expand the market for green products more efficiently. This program has a positive impact on building a sustainable business ecosystem for MSMEs in Cirebon City. Further evaluation is still needed to measure the long-term impact of the implementation of this green marketing strategy.